Gluta laosensis (Anacardiaceae), a new species from Vientiane, Laos - Tagane, Shuichiro; Kameda, Chika; Phouphasouk, Souphachay; Souladeth, Phetlasy (Phytotaxa, 2019)
A new species of Gluta (Anacardiaceae), Gluta laosensis Tagane & Kameda, from Vientiane, Central Laos, is described and illustrated. A new species is easily distinguished from the other species of the genus in Indo-China in having short petioles less than 4 mm long, obovate-oblong or oblong-elliptic leaf blade with rounded to slightly cordate base, and 18–24 pairs of secondary veins.